Chronic urticaria in children: Etiologies, Clinical Manifestations, Diagnosis and Treatment - Javad Ghaffari; Reza Farid Hossaini; Houshang Rafatpanah; Farahzad Jabbari Azad; Soheila Shahmohammadi (Mazandaran University of Medical Sciences, 2013)
Chronic urticaria is defined as a skin disease with central induration (wheal) and erythema formation around it (flare) that appears at least twice a week and remains at least for 6 weeks continually. The incidence of urticaria in children is about 0.1-3%. Most cases of chronic urticaria occur in children between 6-11 years. Autoimmune and allergy immaturity is one of the reasons of lower incidence of chronic urticaria in younger children. Quality of life impairment in children with urticaria has been known to be similar to diseases with severe atopic dermatitis, epilepsy, diabetes mellitus and asthma. There are several causes for chronic urticaria in children in different reports. In most of cases the known etiologic agents are varies from 21 to 83%. Overall, infectious causes of chronic urticaria in children are more common and obvious than other in adults .In most cases, the cause of chronic urticaria are idiopathic or autoimmune. Urticaria severity divided to mild, moderate and severe was based on the number of wheals and severity of pruritus. Diagnosis of chronic urticaria is based on a good history and physical examination. The treatment of chronic urticaria is a patient education that is to remove the triggering and aggravating agents, resolving and treating of the known disease and the use of various medicines based on the history and clinical findings. The first medical therapeutics lines in children are anti-histamines, beta-blocker H1 and new generation of non-sedating agents.